2002
DOI: 10.1002/nbm.735
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus‐31 MR spectroscopy of normal adult human brain and brain tumours

Abstract: Localized phosphorus-31 MR spectra were obtained in vivo in a large series of normal human brain tissue specimens of healthy volunteers (n=36) and various brain tumours (n=52). Tumour types examined included grade II and grade III gliomas (n=15 and n=1, respectively), glioblastomas (n=16) and meningeomas (n=12). An additional eight tumours were analysed during chemo- or radiotherapy. Spectra were acquired using a modified ISIS pulse sequence with a repetition time of 3 s. Voxel sizes ranged from 56 to 129 ml. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
74
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 22 publications
6
74
0
5
Order By: Relevance
“…Previous studies have found significantly high PME/PDE ratio in astrocytoma, metastases and lymphoma compared to controls [13]. But these findings are variable and have limitations as previous studies had also shown increase in both PME and PDE in most tumours , proliferating tissues like regenerating liver, benign tumours and embryo [5].…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Previous studies have found significantly high PME/PDE ratio in astrocytoma, metastases and lymphoma compared to controls [13]. But these findings are variable and have limitations as previous studies had also shown increase in both PME and PDE in most tumours , proliferating tissues like regenerating liver, benign tumours and embryo [5].…”
mentioning
confidence: 92%
“…It detects various metabolites like Phosphomonoesterase (PME), Phosphodiesterase (PDE), inorganic phosphates (Pi), Phosphocreatine (PCr), adenosine triphosphate (ATP) and their ratios like PME/PDE, PME/PCr etc which can be used to characterise tumours. These values may be potentially useful by complimenting the findings of other diagnostic modalities like proton spectroscopy [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…β-ATP piki içerisinde adenozinmonofosfat (AMP) ve adenozindifosfat (ADP) kontaminasyonu olmadığı için, ATP düzeyini tahmin etmekte kullanılır. Metabolik bilgilere ek olarak, 31 P-MRSG'de inorganik fosfat (Pi) ve PCr piklerinin arasındaki frekans farkı kullanılarak hücre içi pH düzeyi hesaplanabilir (6). Proton MR spektroskopisi ile oksijen yetersizliğini ölçmede kullanılan laktat pikinin tespiti aynı frekansta görünen lipid pikleri nedeniyle özel spektral düzenleme planları gerektirirken (7), 31 P MR spektrumu PCr, Pi ve β-ATP piklerinin ölçümü sayesinde iskemik durum hakkında kolayca bir değerlendirme verebilir.…”
Section: Introductionunclassified